Charge adjusting liquid for ceramic substrate

By using charge adjustment solution of polyethylene glycol, fatty acid methyl ethoxylate, triethanolamine and polyquaternary ammonium salt composition with specific structures, the problem of insufficient binding force between the copper layer of the ceramic substrate and the pore wall is solved, and the further development is achieved. Stable copper layer deposition reduces the risk of pore wall separation, improving circuit performance and cost-effectiveness.

CN119265554APending Publication Date: 2025-01-07GUANGDONG LEAR ELECTROCHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411195657.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The electroless plating method of existing ceramic substrates is insufficient in bonding force between the copper layer and the ceramic pore wall, which leads to the problem of pore wall separation and affects the circuit performance.

Method used

Charge adjustment of the pore wall of ceramic substrate is carried out using charge adjustment solution containing polyethylene glycol, fatty acid methyl ethoxylate, triethanolamine, dendritic polyamide amine and specific structures, and subsequent chemistry is enhanced. The bonding force between the copper layer and the ceramic hole wall during the plating process.

Benefits of technology

It effectively improves the bonding force between the copper layer and the ceramic pore wall, reduces the problem of pore wall separation, and ensures the stability and cost-effectiveness of the copper layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The invention belongs to the field of printed circuit board (PCB) ceramic substrate hole metallization, and particularly relates to a charge adjusting liquid of a PCB ceramic substrate, the charge adjusting liquid comprises polyethylene glycol, fatty acid methyl ester ethoxylate, triethanolamine, dendritic polyamidoamine and a polyquaternium composition, charge adjustment can be carried out on the hole wall of the ceramic substrate, and the hole wall of the ceramic substrate can be subjected to hole metallization. And charge adjustment can be carried out on a non-conductive base material with the problems of too large hole wall roughness, glass fiber protrusion and the like caused by poor drilling, palladium is effectively adsorbed in the subsequent process, and then a plating layer with good binding force is formed in the chemical copper plating solution. The in-hole copper layer of the ceramic substrate treated by the charge adjusting liquid has the advantages of difficulty in stripping, good binding force, low cost, high operability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hole metallization of a ceramic substrate of a circuit board (PCB), and in particular relates to a charge adjusting liquid of a PCB ceramic substrate. Background Art

[0002] PCB ceramic substrate is a special circuit board with excellent electrical insulation, high thermal conductivity and excellent welding performance. Based on its unique properties, ceramic substrate has a large current carrying capacity. Ceramic substrate has become the basic material for high-power power circuit structure technology and interconnection technology. It has the characteristics of strong mechanical stress, stable shape, no pollution, no pollution, low thermal expansion coefficient and wide operating temperature. Based on its good performance, many important electronic devices with large current load use it as the core material. The current hole metallization processing methods of ceramic plates are divided into thin film method, thick film method, direct copper coating method, laser activated metallization method and chemical plating method. Its processing is highly affected by process capabilities. The chemical copper deposition method can be used for large-scale production with low cost, but the bonding strength between the copper layer and the ceramic pore wall is the difficulty in its preparation. In order to strengthen the bonding strength between the chemically deposited copper layer and the ceramic wall and solve the performance drawbacks of ceramic substrates formed by chemical plating, it is particularly important to develop a charge adjustment liquid for ceramic substrates. Before chemical deposition, the pore wall of the ceramic substrate is charge adjusted so that the palladium layer can be effectively adsorbed and activated in the subsequent process, and then the bonding strength between the deposited copper layer and the ceramic pore wall can be enhanced during chemical plating.

[0003] There is an urgent need for a charge adjustment liquid with superior performance. After the charge adjustment treatment of the ceramic substrate, the bonding strength between the deposited copper layer and the ceramic pore wall can be improved and the problem of pore wall separation can be reduced. Summary of the invention

[0004] In order to deposit a copper layer with good bonding strength on the hole wall of a ceramic plate, the present invention provides a charge adjustment liquid for a ceramic substrate, wherein the charge adjustment liquid comprises polyethylene glycol, fatty acid methyl ester ethoxylate, triethanolamine, dendritic polyamidoamine (PAMAM), and a polyquaternary ammonium salt composition; the polyquaternary ammonium salt composition comprises polyquaternary ammonium salt-1, polyquaternary ammonium salt-11, and a polyquaternary ammonium salt having the following general formula (I): ; In the general structure (I), R is selected from methyl, ethyl, propyl, 2-propyl, 2-butyl, pentyl, 2-pentyl, 3-pentyl, hexyl, 2-hexyl, 3-hexyl, heptyl, 2-heptyl, 3-heptyl, 4-heptyl, octyl, 2-octyl, 3-octyl, 4-octyl, nonyl, 2-nonyl, 3-nonyl, 4-nonyl, 5-nonyl, decyl, 2-decyl, 3-decyl, 4-decyl, 5-decyl, benzyl, 2-methylbenzyl, 3-methylbenzyl, 4-methylbenzyl, 3,5-dimethylbenzyl, 2-methoxybenzyl, 3-methoxybenzyl, 4-methoxybenzyl, 2-nitrobenzyl, 3-nitrobenzyl any one of 4-nitrobenzyl, 2-trifluoromethylbenzyl, 2-chlorobenzyl, 3-chlorobenzyl, 4-chlorobenzyl, 2-bromobenzyl, 3-bromobenzyl, 4-bromobenzyl, 2-fluorobenzyl, 3-fluorobenzyl, 4-fluorobenzyl, 3-trifluoromethylbenzyl, 4-trifluoromethylbenzyl, phenethyl, phenylpropyl, allyl, allyl, 3-fluoro-5-trifluoromethylbenzyl, 3-fluoro-4-nitrobenzyl, 2-chloro-4,5-difluorobenzyl bromide, 2-ethylbenzyl, 3-ethylbenzyl, 4-ethylbenzyl, 2,6-difluoro-4-methoxybenzyl, and 2,6-difluoro-4-methoxy, wherein n is 2-15.

[0005] As a preferred technical solution, the concentration of polyethylene glycol in the charge adjustment liquid is 4-5 g / L, the concentration of fatty acid methyl ester ethoxylate is 1-3 g / L, the concentration of triethanolamine is 1-5 g / L, the concentration of dendritic polyamidoamine (PAMAM) is 0.01-0.1 g / L, and the concentration of the polyquaternary ammonium salt composition is 0.1-15 g / L.

[0006] As a preferred technical solution, the molecular weight of the polyethylene glycol is 1500, and the molecular weight of the dendritic polyamidoamine (PAMAM) is between 517-1167493.

[0007] As a preferred technical solution, the mass ratio of the polyquaternium salt-1, the polyquaternium salt-11 and the polyquaternium salt of general formula (I) is 1:(1-3):(1-10).

[0008] As a preferred technical solution, the preparation method of the polyquaternary ammonium salt of the general formula (I) is: S1 Add piperazine and anhydrous ethanol into a flask, and then place it on a stirrer for stirring. The temperature is controlled at 15-30℃; S2 Add N,N-methylenebisacrylamide to the flask in step S1 in 5 batches, with a time interval of 5-20 minutes between each addition, ensuring that the temperature does not exceed 35°C, and continue the reaction for 2-10 hours; S3: Place the flask of S2 in a heating device at 78°C, add an inorganic strong base, and add an organic halide of the following general formula (II) to react for 6-24 hours; R1-X (II) In the general formula (II), X is any one of chlorine, bromine and iodine, and R1 is selected from methyl, ethyl, propyl, 2-propyl, 2-butyl, pentyl, 2-pentyl, 3-pentyl, hexyl, 2-hexyl, 3-hexyl, heptyl, 2-heptyl, 3-heptyl, 4-heptyl, octyl, 2-octyl, 3-octyl, 4-octyl, nonyl, 2-nonyl, 3-nonyl, 4-nonyl, 5-nonyl, decyl, 2-decyl, 3-decyl, 4-decyl, 5-decyl, benzyl, 2-methylbenzyl, 3-methylbenzyl, 4-methylbenzyl, 3,5-dimethylbenzyl, 2-methoxybenzyl, 3-methoxybenzyl, 4-methoxybenzyl, 2-nitrobenzyl, 3-nitrobenzyl, 4-nitrobenzyl, 2-trifluoromethylbenzyl, 2-chlorobenzyl, 3-chlorobenzyl, 4-chlorobenzyl, 2-bromobenzyl, 3-bromobenzyl, 4-bromobenzyl, 2-fluorobenzyl, 3-fluorobenzyl, 4-fluorobenzyl, 3-trifluoromethylbenzyl, 4-trifluoromethylbenzyl, phenethyl, phenylpropyl, allyl, allyl, 3-fluoro-5-trifluoromethylbenzyl, 3-fluoro-4-nitrobenzyl, 2-chloro-4,5-difluorobenzyl bromide, 2-ethylbenzyl, 3-ethylbenzyl, 4-ethylbenzyl, 2,6-difluoro-4-methoxybenzyl, 2,6-difluoro-4-methoxy; S4 After the reaction is completed, add pure water and stir. The mixed solution can be used without purification.

[0009] As a preferred technical solution, in the synthesis of the polyquaternary ammonium salt of general formula (I), the molar mass ratio of piperazine to bisacrylamide is (0.5-2):1.

[0010] As a preferred technical solution, the amount of anhydrous ethanol in S1 is 13-10 times the total amount of piperazine, N,N-methylenebisacrylamide, inorganic base and organic halide in steps S1-S4, and the amount of water in S4 is 1 times the amount of anhydrous ethanol in S1.

[0011] As a preferred technical solution, the input amount of the S3 inorganic strong base is 2-3 times the molar input amount of piperazine, and the input amount of the organic halide is 2-3 times the molar input amount of piperazine.

[0012] As a preferred technical solution, the inorganic base is NaOH.

[0013] As a preferred technical solution, the inorganic base is KOH.

[0014] Beneficial Effects The charge adjustment liquid for ceramic-based PCB provided by the present invention contains a cationic polymer, a quaternary ammonium salt composition, a fatty acid methyl ester ethoxylate, and triethanolamine, and can be used to adjust the charge on the hole wall of a ceramic substrate, and can also be used to adjust the charge on a non-conductive substrate with problems such as excessive hole wall roughness and protruding glass fibers due to poor drilling, effectively adsorb palladium in a subsequent process, and then form a coating with good bonding strength in a chemical copper plating solution. The copper layer in the hole of the ceramic substrate treated with the charge adjustment liquid has the advantages of being difficult to peel off, having good bonding strength, being low in cost, and being highly operable. DETAILED DESCRIPTION

[0015] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Example 1 Preparation of polyquaternary ammonium salt of general formula (I): ;

[0017] 1) Add 0.1 mol piperazine and 150 ml anhydrous ethanol into a flask, then place it on a stirrer and stir it in a water bath at 25°C; 2) Add 0.1 mol N,N-methylenebisacrylamide into the flask in step S1 in 5 batches, with an interval of 5 minutes between each batch, ensuring that the temperature does not exceed 35°C, and continue the reaction for 2 hours; 3) Place the flask in 2) in a heating device at 78°C, add 0.25 mol NaOH and 0.2 mol propylene chloride, and react for 10 hours; 4) After the reaction is completed, 150 ml of pure water is added and stirred evenly to obtain a polyquaternary ammonium salt solution. The polyquaternary ammonium salt solution can be used without purification, and its effective content is 31.8 g. The product obtained in this example is named a1.

[0018] Example 2 Preparation of polyquaternary ammonium salt of general formula (I): ;

[0019] 1) Add 0.1 mol piperazine and 200 ml anhydrous ethanol into a flask, then place it on a stirrer and stir it in a water bath at 25°C; 2) Add 0.1 mol N,N-methylenebisacrylamide into the flask in step S1 in 5 batches, with an interval of 5 minutes between each batch, ensuring that the temperature does not exceed 35°C, and continue the reaction for 2 hours; 3) Place the flask in 2) in a heating device at 78°C, add 0.25 mol NaOH and 0.2 mol methyl bromide, and react for 8 hours; 4) After the reaction is completed, 200 ml of pure water is added and stirred evenly to obtain a polyquaternary ammonium salt solution. The polyquaternary ammonium salt solution can be used without purification, and its effective content is 27 g. The product obtained in this example is named a2.

[0020] Example 3 Preparation of polyquaternary ammonium salt of general formula (I): ;

[0021] 1) Add 0.08 mol piperazine and 200 ml anhydrous ethanol into a flask, then place it on a stirrer and stir it in a water bath at 25°C; 2) Add 0.1 mol N,N-methylenebisacrylamide into the flask in step S1 in 5 batches, with an interval of 5 minutes between each batch, ensuring that the temperature does not exceed 35°C, and continue the reaction for 2 hours; 3) Place the flask in 2) in a heating device at 78°C, add 0.25 mol NaOH and 0.18 mol methyl bromide, and react for 8 hours; 4) After the reaction is completed, 200 ml of pure water is added and stirred evenly to obtain a polyquaternary ammonium salt solution. The polyquaternary ammonium salt solution can be used without purification, and its effective content is 25 g. The product obtained in this example is named a3.

[0022] Example 4 Preparation of polyquaternary ammonium salt of general formula (I): ;

[0023] 1) Add 0.1 mol piperazine and 200 ml anhydrous ethanol into a flask, then place it on a stirrer and stir it in a water bath at 25°C; 2) Add 0.11 mol N,N-methylenebisacrylamide into the flask in step S1 in 5 batches, with an interval of 5 minutes between each batch, ensuring that the temperature does not exceed 35°C, and continue the reaction for 2 hours; 3) Place the flask in 2) in a heating device at 78°C, add 0.25 mol NaOH and 0.2 mol ethyl bromide, and react for 8 hours; 4) After the reaction is completed, 200 ml of pure water is added and stirred evenly to obtain a polyquaternary ammonium salt solution. The polyquaternary ammonium salt solution can be used without purification, and its effective content is 29.3 g. The product obtained in this example is named a4.

[0024] Example 5 Preparation of polyquaternary ammonium salt of general formula (I):

[0025] 1) Add 0.1 mol piperazine and 200 ml anhydrous ethanol into a flask, then place it on a stirrer and stir it in a water bath at 25°C; 2) Add 0.09 mol N,N-methylenebisacrylamide into the flask in step S1 in 5 batches, with an interval of 5 minutes between each batch, ensuring that the temperature does not exceed 35°C, and continue the reaction for 2 hours; 3) Place the flask in 2) in a heating device at 78°C, add 0.25 mol NaOH and 0.2 mol ethyl bromide, and react for 8 hours; 4) After the reaction is completed, 200 ml of pure water is added and stirred evenly to obtain a polyquaternary ammonium salt solution. The polyquaternary ammonium salt solution can be used without purification, and its effective content is 26.3 g. The product obtained in this example is named a5.

[0026] Embodiment 6-20 Example 6-20 is a charge adjustment solution prepared by mixing the polyquaternium salt a1-5 prepared in Example 1-5 with polyethylene glycol, fatty acid methyl ester ethoxylate, triethanolamine, dendritic polyamidoamine, polyquaternium salt-1, and polyquaternium salt-11, wherein the polyquaternium salt a1-5 is mixed and then added in the amount required in Example 6-20. The detailed ratio is shown in Table 1.

[0027] Table 1 Preparation of charge adjustment solution of Example 6-20

[0028] Comparative Example 1-15 is a charge adjustment solution prepared by combining polyethylene glycol, fatty acid methyl ester ethoxylate, triethanolamine, dendritic polyamidoamine, polyquaternium-1, and polyquaternium-11 without the polyquaternium salt a1-5 prepared in Example 1-5. The detailed proportions are shown in Table 2.

[0029] Table 2 Preparation of charge adjustment solution of comparative examples 1-15

[0030] Embodiment 21 The test piece of ceramic plate is 6cm The size of 6cm and the thickness of 3mm are, and the processing flow is charge adjustment → pre-dip → activation → acceleration → copper deposition → degreasing → electroplating. The charge adjustment is adjusted by the charge adjustment liquid provided in the embodiment and the comparative example. The pre-dip electroplating process is the corresponding products and parameters provided by Guangdong Lier Chemical Co., Ltd., and the detailed products are shown in Table 3. After the electroplating is completed, a thermal shock test is performed at 288°C, 10s, 7 times, and the other parameters of the thermal shock are performed using the known technology in the art. Investigate whether there is a problem of hole wall separation.

[0031] Table 3 Test process parameters of ceramic plate test board

[0032] The test results of Examples 6-20 and Comparative Examples 1-15 are shown in Table 4. The deposition rate and backlight tests are performed according to the known techniques in the art. If the test results show no hole wall separation problem, it is recorded as OK. If the test results show hole wall separation problem, it is recorded as NG.

[0033] Table 4 Test results of embodiments and comparative examples

[0034] According to the test results in Table 4, the deposition rate and backlight of the test results of Examples 6-20 are good, and the thermal shock test results of the test pieces meet the requirements of process quality. The deposition rate and backlight in Comparative Examples 1-15 are good, but the thermal shock test has an abnormal problem of pore wall separation. It can be seen that adding a polyquaternary ammonium salt having the above-mentioned general formula (I) structure to the charge adjustment liquid can effectively enhance the bonding force between the deposited copper layer and the ceramic pore wall and reduce the abnormal problem of pore wall separation. The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A charge adjustment liquid for a ceramic substrate, characterized in that: The charge adjustment liquid comprises polyethylene glycol, fatty acid methyl ester ethoxylate, triethanolamine, dendritic polyamidoamine, and a polyquaternary ammonium salt composition; the polyquaternary ammonium salt composition comprises polyquaternary ammonium salt-1, polyquaternary ammonium salt-11, and a polyquaternary ammonium salt having the following general formula (I): ; In the general structure (I), R is selected from methyl, ethyl, propyl, 2-propyl, 2-butyl, pentyl, 2-pentyl, 3-pentyl, hexyl, 2-hexyl, 3-hexyl, heptyl, 2-heptyl, 3-heptyl, 4-heptyl, octyl, 2-octyl, 3-octyl, 4-octyl, nonyl, 2-nonyl, 3-nonyl, 4-nonyl, 5-nonyl, decyl, 2-decyl, 3-decyl, 4-decyl, 5-decyl, benzyl, 2-methylbenzyl, 3-methylbenzyl, 4-methylbenzyl, 3,5-dimethylbenzyl, 2-methoxybenzyl, 3-methoxybenzyl, 4-methoxybenzyl, 2-nitrobenzyl, 3-nitrobenzyl, 4-nitrobenzyl, 2-trifluoromethylbenzyl, 2-chlorobenzyl, 3-chlorobenzyl, 4-chlorobenzyl, 2-bromobenzyl, 3-bromobenzyl, 4-bromobenzyl, 2-fluorobenzyl, 3-fluorobenzyl, 4-fluorobenzyl, 3-trifluoromethylbenzyl, Any one of fluoromethylbenzyl, 4-trifluoromethylbenzyl, phenethyl, phenylpropyl, allyl, butylene, 3-fluoro-5-trifluoromethylbenzyl, 3-fluoro-4-nitrobenzyl, 2-chloro-4,5-difluorobenzyl bromide, 2-ethylbenzyl, 3-ethylbenzyl, 4-ethylbenzyl, 2,6-difluoro-4-methoxybenzyl, 2,6-difluoro-4-methoxy, wherein n is 2-15.

2. The charge adjustment liquid for a ceramic substrate according to claim 1, characterized in that: The concentration of polyethylene glycol in the charge adjustment solution is 4-5 g / L, the concentration of fatty acid methyl ester ethoxylate is 1-3 g / L, the concentration of triethanolamine is 1-5 g / L, the concentration of dendritic polyamidoamine is 0.01-0.1 g / L, and the concentration of polyquaternary ammonium salt composition is 0.1-15 g / L.

3. The charge adjustment liquid for a ceramic substrate according to claim 1 or 2, characterized in that: The molecular weight of the polyethylene glycol is 1500, and the molecular weight of the dendritic polyamidoamine is between 517 and 1167493.

4. The charge adjustment liquid for a ceramic substrate according to claim 3, characterized in that: The mass ratio of the polyquaternium salt-1, the polyquaternium salt-11 and the polyquaternium salt of general formula (I) is 1:(1-3):(1-10).

5. The charge adjustment liquid for a ceramic substrate according to claim 4, characterized in that: The preparation method of the polyquaternary ammonium salt of the general formula (I) is: S1 Add piperazine and anhydrous ethanol into a flask, and then place it on a stirrer for stirring. The temperature is controlled at 15-30℃; S2 Add N,N-methylenebisacrylamide to the flask in step S1 in 5 batches, with a time interval of 5-20 minutes between each addition, ensuring that the temperature does not exceed 35°C, and continue the reaction for 2-10 hours; S3: Place the flask of S2 in a heating device at 78°C, add an inorganic strong base, and add an organic halide of the following general formula (II) to react for 6-24 hours; R1-X (II) In the general formula (II), X is any one of chlorine, bromine and iodine. R1 is selected from the group consisting of methyl, ethyl, propyl, 2-propyl, 2-butyl, pentyl, 2-pentyl, 3-pentyl, hexyl, 2-hexyl, 3-hexyl, heptyl, 2-heptyl, 3-heptyl, 4-heptyl, octyl, 2-octyl, 3-octyl, 4-octyl, nonyl, 2-nonyl, 3-nonyl, 4-nonyl, 5-nonyl, decyl, 2-decyl, 3-decyl, 4-decyl, 5-decyl, benzyl, 2-methylbenzyl, 3-methylbenzyl, 4-methylbenzyl, 3,5-dimethylbenzyl, 2-methoxybenzyl, 3-methoxybenzyl, 4-methoxybenzyl, 2-nitrobenzyl, 3-nitrobenzyl, 4-nitrobenzyl, 2-trifluoromethylbenzyl, 2-chlorobenzyl, 3-chlorobenzyl, 4-chlorobenzyl, 2-bromobenzyl, 3-bromobenzyl, 4-bromobenzyl, 2-fluorobenzyl, 3-fluorobenzyl, 4-fluorobenzyl, 3-trifluoromethylbenzyl, 4-trifluoromethylbenzyl, phenethyl, phenylpropyl, allyl, allyl, 3-fluoro-5-trifluoromethylbenzyl, 3-fluoro-4-nitrobenzyl, 2-chloro-4,5-difluorobenzyl bromide, 2-ethylbenzyl, 3-ethylbenzyl, 4-ethylbenzyl, 2,6-difluoro-4-methoxybenzyl, 2,6-difluoro-4-methoxy; S4 After the reaction is completed, add pure water and stir. The mixed solution can be used without purification.

6. The charge adjustment liquid for a ceramic substrate according to claim 5, characterized in that: In the synthesis of the polyquaternary ammonium salt of the general formula (I), the molar mass ratio of piperazine to bisacrylamide is (0.5-2):

1.

7. The charge adjustment liquid for a ceramic substrate according to claim 5, characterized in that: The amount of anhydrous ethanol in S1 is 13-10 times the total amount of piperazine, N,N-methylenebisacrylamide, inorganic base and organic halide in steps S1-S4, and the amount of water in S4 is 1 times the amount of anhydrous ethanol in S1.

8. The charge adjustment liquid for a ceramic substrate according to claim 5, characterized in that: The feed amount of the S3 inorganic strong base is 2-3 times the molar feed amount of piperazine, and the feed amount of the organic halide is 2-3 times the molar feed amount of piperazine.

9. The charge adjustment liquid for a ceramic substrate according to claim 5, characterized in that: The inorganic base is NaOH.

10. The charge adjustment liquid for a ceramic substrate according to claim 5, characterized in that: The inorganic base is KOH.